An Inventive Wisconsin: Ingenuity, Enterprise, and the Knowledge Economy - Still, Tom (My University, 2007)
Tom Still will talk about the work of the Wisconsin Technology Council, which serves as the independent science and technology advisor to the governor and the state legislature and addresses Wisconsin's strengths and challenges in the 21st Century knowledge economy. Among the opportunities facing Wisconsin are ways to cultivate the ingenuity, inventiveness, and enterprise of people across the state by inviting them to come to campus experience science as a way of exploring the unknown.
Keywords: Entrepeneurial University; Outreach, Engagement, and the Public Good